The Use of Botulinum Toxin in Dental Practice - Xakimova Zilolaxon Qahramonjonovna (Genius Journals, 2022)
Today, in the field of medical technology, there has been a concept for the development of minimally invasive methods of treatment, while reducing the frequency of surgical interventions, the risk of development and the severity of complications. One of thesemethods is the use of botulinum toxin preparations in dentistry and maxillofacial surgery
Keywords: botulinum, dental diseases, treatment, diagnosis, method